Finding a Voice : Men in Eudora Welty's "Flowers for Marjorie" and "Where is the Voice Coming from" - Taher, Isra Hashim (جامعة بغداد - كلية الآداب, 2014)
تصنف الكاتبة الأمريكية (يودورا ويلتي) (1909 - 2001) على أنها كاتبة للرواية القوطية الجنوبية والتي من أبرز شخصياتها نساء على الرغم من كون بعضهن غريبات وقبيحات بينما يبدو الرجال عاجزين وهامشيين. في قصص قصيرة مثل "ورود لميرجوري" و "من أين يأتي الصوت" تبدو الشخصيات الرئيسية عنيفة ووحيدة وتبحث عن الاعتراف بها. تصف (يودورا ويلتي) في سيرتها الذاتية بداية كاتب واحد (1983) دخولها العالم الأدبي حيث تقسم كتابها إلى ثلاثة أقسام تحمل تباعا العنوانين "الاستماع" و "تعلم التبصر" و "إيصال الصوت". تدرك الكاتبة في القسم الأول إن الاستماع إلى قصص العائلة والأصدقاء والمعلمين هو أول ما يلزمها في مهنتها الأدبية. وفي القسم الثاني تتعلم من خلال السفر أشياء جديدة عن والديها وتكتشف أيضا حرفتها وتجد ضالتها بالقصة القصيرة. وفي القسم الثالث تصف نجاحها في التعبير عن نفسها من خلال الفن وبالأخص الرواية. وفي كتاباتها يبدو إن (ويلتي) قد استخدمت ومن غير قصد ما ادعوه "صيغة الإقرار" وذلك لعدم وجود مصطلح آخر. وفي "ورود لميرجوري" و "من أين يأتي الصوت" تستخدم صيغة الاستماع وتعلم التبصر وإيصال الصوت" بشكل مختلف. إن هدف هذا البحث هو التحقق من كيفية استخدام (ويلتي) لهذه الصيغة في هاتين القصتين القصيرتين الأقل شهرة بين قصصها القصيرة حيث يحاول شخوصها الرجال وبشدة إيصال صوتهم. The American writer Eudora Welty (1909-2001) is often labeled as a Southern Gothic fiction writer whose most memorable characters are women, though some of them are grotesque and ugly. Her men, on the other hand, appear to be powerless and marginalized. In short stories like "Flowers for Marjorie" and "Where is the Voice Coming From" the protagonists are grotesquely violent, lonely, and searching for recognition. In her autobiography, One Writer's Beginning (1983), Welty describes her initiation into the literary world. She divides her book into three sections that respectively carry the titles of "Listening", "Learning to See " and "Finding a Voice". In the first section she realizes that listening to stories told by family, friends, and teachers, is the first thing she needs in order to establish her literary career. In "Learning to See" section she learns, through traveling, new things about her parents. She also discovers her calling and finds her form: the short story. In the final section she describes how she succeeds in expressing herself through art, namely, fiction. In her writing, it seems that Welty has unconsciously employed what I call for the lack of a better term, "the formula of recognition". In "Flowers for Marjorie" and "Where is the Voice Coming From" she variously uses the "listening, learning to see, and finding a voice." The aim of this paper is to investigate how Welty uses this formula in these two least famous among her short stories, where the main male characters fervently try to find a voice.
Keywords: القصص القصيرة الأمريكية -- الأدباء الأمريكان -- يودورا ويلتي -- الاعمال الادبية -- النقد الادبي